THE EFFECT OF ALOE VERA WASTE LIQUID ORGANIC FERTILIZER ON THE GROWTH AND YIELDS OF BABY CUCUMBERS IN PEAT SOIL - EFI .; Rahmidiyani .; Warganda . (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to determine the effect of aloe vera waste liquid fertilizer on the growth and yield of baby cucumbers on peat soil. The study was conducted in the Pontianak from May 5, 2019 to June 14, 2019. The method of the study was designed in a Completely Randomized Design (CRD) with one factor, i.e. the concentration of Aloe vera waste manure, which consisted of 5 treatments with 5 replications and each replication consisted of 5 sample plants. The treatment were set as p1 = 3%, p2 = 5%, p3 = 7%, p4 = 9%, p5 = 11% of aloe vera waste manure were applied by watering directly on to the peat soil media with 600 ml/liter of water correspond to soil field capacity. The variables observed in this study were root volume, root dry weight, dry weight of the plant shoot, number of fruits per plant, fruit diameter, weight per fruit and weight of fruit per plant. The results showed that the application of aloe vera waste liquid manure have increased the growth and yield of baby cucumbers grown in peat soil. It was concluded that the application of 7% concentration of aloe vera waste manure was noted as an effective concentration for the growth, and weight of baby cucumber fruits. Keywords: baby cucumber, peat soil, aloe vera waste, liquid organic fertilizer,